Reconstruções ósseas horizontais orais com enxerto de A-PRF+, I-PRF e osso alógeno particulado e sua relação com características demográficas e de saúde dos pacientes - Zanini, Francielle Aimi (2019)
Introduction: Bone resorption is a common physiological process after tooth loss and it is often necessary to reconstruct the region with bone grafts prior to implant installation. PRF has been used in several dental procedures in recent decades and more recently as an alternative for horizontal increases in conjunction with biomaterials. Purpose: To study possible associations between bone gain and percentage of reabsorption of regions reconstructed horizontally by graft technique with particulate allogeneic bone, A-PRF + and i-PRF, supported by screws with the demographic and health characteristics of the patients. Methods: A retrospective cohort study was performed by analyzing medical records and CT scans of patients submitted to reconstructive procedures for horizontal augmentation with particulate allogenic bone, A-PRF + and i-PRF supported by screws. Pre and post graft tomography measurements were performed to evaluate bone gain in millimeters and percentage of resorption. In addition, histological analysis of 5 fragments obtained from patients submitted to grafting with the technique studied was performed. Results: The majority of patients in the sample were female (75%) and the mean age was 57 years (SD = 8,3). Implants were installed in all reconstructed regions, and 49.4% required complementary grafting at implant placement. The mean bone gain was 2.64 mm (SD = 1.16) and the mean resorption percentage was 33.4% (SD = 22.71). In the association analysis, men presented a statistically higher percentage of resorption and patients over the median age (57 years) had a greater need for a new graft. The presence of hypertension was not associated with any variable. Histologically, neoformed bone tissue with no sign of inflammation was observed in all cases. Conclusion: Reconstructed regions with allogenic bone, A-PRF + and i-PRF had sufficient bone gains for the implant installation, although with the need for a complementary graft in some cases. Gender was statistically associated with resorption while age was associated with the need for a new graft.